Research on Network Selection Algorithm Based on User Preference in Heterogeneous System - Cun Yang; Jihong Zhao; Shuyuan Zhao (Dianxin kexue)
Most network selection algorithms did not pay more attention to user preference for networks which was based on service requirements.For this circumstance,a new network selection algorithm based on user prefenence was proposed.The algorithm was fully considerd service reqirements,user prefernece and network performance.The AHP algorithm and distance analysis were used to calculate subjective and objective user preference weight respectively for different heterogeneous networks.Then the user preference weight for networks could be obtained dynamically on the basis of user strategy.The performance of each candidate network was counted,based on which the optimum network was selected.Simulation results show that the algorithm performs well in network selection and reduces the number of handoff times as the user moves through the network boundary frequently.